Production costs of apple - Kreus, Carlos Leomar (Pesquisa Agropecuaria Brasileira, 1992)
The present study tries to answer questions concerning the production costs of apples. Based on data obtained in the region of 'Alto Vale do Rio do Peixe', Santa Catarina, Brazil, it was determined that the production costs of 1 kg of apples are aproximatelly 0.02 OTN (1 OTN = US$ 7.70 in November 1987). Therefore, apple in that State, belongs to the group of agricultural products with the highest production costs.
Keywords: Malus domestica; apple tree; orchard